Synthesis of Silver Nanoparticles Using Vaccinium Macrocarpon and Investigation of its Role as an Antibacterial Agent - Dhannoon, Nour Abdulehsan (American Journal of Biology and Natural Sciences, 2025)
Background & aim: Current applications for silver (Ag) nanoparticles include medication delivery, biomedicine, parasitology, antibacterial, antifungal, and anti-biofilm. Therefore, the current study aimed to create silver nanoparticles using Vaccinium macrocarpon extract and to study its role as an antibacterial agent against Gram-negative bacteria. Materials & Methods: V. macrocarpon fruits were collected from various local markets from April 25 to June 25, 2025. The nanoparticles were synthesized using 1 mM AgNO3 with V. macrocarpon fruit extract. After studying the properties of the silver nanoparticles, a test was conducted against two types of bacteria, Staphylococcus aureus and Escherichia coli, using an agar well diffusion experiment to detect whether there was an antibacterial effect of the silver nanoparticles. Results: After synthesizing silver nanoparticles, their properties were studied and A broad absorption peak of Ag NPs was detected at a wavelength of 436 nm by using UV-Vis spectrophotometer. FT-IR analysis revealed biomolecules that efficiently encapsulated and stabilized the Ag NPs produced by V. macrocarpon. E. coli isolates showed high susceptibility to Ciprofloxacin (86.2%) and Gentamicin (80.4%) but very low to Ampicillin (2.6%) and Vancomycin (0%). S. aureus isolates were highly susceptible to Vancomycin (94.2%), Ciprofloxacin (90.8%), and Gentamicin (86.4%), with low susceptibility to Ampicillin (3.2%). The size range of the produced AgNPs in the sample is 58–337 nm by using scanning electron microscopy (SEM). Using the agar well diffusion method, the antibacterial activity of AgNPs against two species was found to be effective against S. aureus and E. coli. Regarding their capacity to inhibit the growth of microorganisms, AgNPs performed better than plant extract. The highest inhibition against S. aureus (17) mm and E. coli (39) mm was demonstrated by AgNPs. Conclusions: The current study described a rapid, simple, safe, affordable, and environmentally friendly process for creating Ag NPs utilizing fruit extract from V. macrocarpon, and the results of this study suggest that Ag NPs can be utilized to make antibacterial drugs.